Umbilical Cord Mesenchymal Stem Cell Transplantation Prevents Chemotherapy-Induced Ovarian Failure via the NGF/TrkA Pathway in Rats. (23rd May 2019) - Zheng, Qun; Fu, Xiaoyan; Jiang, Jinzhan; Zhang, Ning; Zou, Libo; Wang, Wenqian; Ding, Mingxing; Chen, Haohao
Abstract : Chemotherapy leads to a loss of fertility and reproductive endocrine function, thereby increasing the risk of premature ovarian failure (POF). Studies have suggested that the transplantation of mesenchymal stem cells could inhibit apoptosis in ovarian granulosa cells and improve follicular development. In the present study, the effects of human umbilical cord mesenchymal stem cell (UCMSC) transplantation on ovarian function after ovarian damage caused by chemotherapy and the mechanism underlying these effects were investigated. POF model rats were obtained by the intraperitoneal injection of cyclophosphamide, and cultured UCMSCs were transplanted by tail vein injection. Serum estrogen, follicle-stimulating hormone, gonadotropin releasing hormone, and anti-Mullerian hormone levels were detected by ELISA. Folliculogenesis was evaluated by histopathological examination. The expression levels of nerve growth factor (NGF), high affinity nerve growth factor receptor (TrkA), follicle-stimulating hormone receptor (FSHR), and caspase-3 were evaluated by western blotting and RT-qPCR. The natural reproductive capacity was assessed by pregnant rate and numbers of embryos. The results indicated that UCMSC transplantation recovered disturbed hormone secretion and folliculogenesis in POF rats. NGF and TrkA levels increased, while FSHR and caspase-3 decreased. The pregnancy rate of POF rats was improved. Therefore, UCMSCs could reduce ovarian failure due to premature senescence caused by chemotherapy, and the NGF/TrkA signaling pathway was involved in the amelioration of POF.